Odpowiedzi

2010-03-13T13:07:54+01:00
P=60m2

a=12m
b=5m

a=3dm=0.3m
b=200dm

a=20km=20000m
b=0.003m

a=2mm=0.002m
b=30000m
4 5 4
Najlepsza Odpowiedź!
2010-03-13T13:09:23+01:00
P(prostokąta) = a*b
a = 12 m
12*b=60
60/12=5
12*5=60
b=60

P(prostokąta) = a*b
a=3dm = 0,3 m
0,3*b=60
60/0,3=200
b=200

P(prostokąta) = a*b
a=20 km = 20000 m
20000 *b = 60
60\20000=0,003
b=0,003

P(prostokąta)=a*b
a=2mm=0,2cm=0,002m
0,002m*b=60
60\0,002m = 30000
b=30000


5 5 5
2010-03-13T13:10:07+01:00
P = 60m²
p = a*b
a.) 60:12 = 5m
b.) 3dm = 0,3m
60:0,3 = 200m
c.) 20km = 20000m
60:20000 = 0,003m
d.) 2mm = 0,02m
60:0,02 = 3000m
3 5 3